Human Genetic Host Factors and Its Role in the Pathogenesis of Chikungunya Virus Infection - Rueda, Juan C.; Arcos-Burgos, Mauricio; Santos, Ana M.; Martin-Arsanios, Daniel; Villota-Erazo, Catalina; Reyes, Viviana; Bernal-Macías, Santiago; Peláez-Ballestas, Ingris; Cardiel, Mario H.; Londono, John (Frontiers in Medicine, 2022)
Chikungunya virus (CHIKV) is an alphavirus from the Togaviridae family that causes acute arthropathy in humans. It is an arthropod-borne virus transmitted initially by the Aedes (Ae) aegypti and after 2006’s epidemic in La Reunion by Ae albopictus due to an adaptive mutation of alanine for valine in the position 226 of the E1 glycoprotein genome (A226V). The first isolated cases of CHIKV were reported in Tanzania, however since its arrival to the Western Hemisphere in 2013, the infection became a pandemic. After a mosquito bite from an infected viremic patient the virus replicates eliciting viremia, fever, rash, myalgia, arthralgia, and arthritis. After the acute phase, CHIKV infection can progress to a chronic stage where rheumatic symptoms can last for several months to years. Although there is a great number of studies on the pathogenesis of CHIKV infection not only in humans but also in animal models, there still gaps in the proper understanding of the disease. To this date, it is unknown why a percentage of patients do not develop clinical symptoms despite having been exposed to the virus and developing an adaptive immune response. Also, controversy stills exist on the pathogenesis of chronic joint symptoms. It is known that host immune response to an infectious disease is reflected on patient’s symptoms. At the same time, it is now well established that host genetic variation is an important component of the varied onset, severity, and outcome of infectious disease. It is essential to understand the interaction between the aetiological agent and the host to know the chronic sequelae of the disease. The present review summarizes the current findings on human host genetics and its relationship with immune response in CHIKV infection.